PAPARAN IKLAN JUNK FOOD DAN POLA KONSUMSI JUNK FOOD SEBAGAI FAKTOR RISIKO TERJADINYAOBESITAS PADA ANAK SEKOLAH DASAR KOTA DAN DESA DI DAERAH ISTIMEWA YOGYAKARTA - , Esti Nurwanti; , Prof. dr. Hamam Hadi, MS, Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The childhood obesity has been an epidemic in both developed and developing countries including Indonesia. Whether exposure to junk food ads is associated with the increased obesity prevalence in Indonesian school children remains unclear. Objective : to examine exposure to junk food ads and energy intake from junk food as risk factors of obesity in Indonesian elementary school children. Design : A case-control study of 244 obese and 244 non obese children was conducted in Yogyakarta municipality in 2012. Cases were elementary school children with BMI/ Age > 95th percentile identified in previous survey. Controls were children from the same class and seating at the right side nearest to the cases. Weight and standing height were by trained nutritionists. Data on exposure to junk food ads were obtained by multipliying duration of tv viewing of each child to the mean advertisment of junk food per-day. BMI of the study subjects were computed using WHO Anthro2005 software. Statistical analysis was done using STATA 11th edition software. Result : Elementary school children who were exposed to junk food ads â¥49/day were 1.6 (OR=1.6, 95% CI=1.1-2.4) more likely to be obese than those exposed to junk food ads <49/day. Energy intake from junk food was not significantly associated with childhood obesity. Conclusion : Exposure to junk food advertising was proven to be significantly associated with the increased risk of obesity in Indonesian elementary school children.